Cultural violence and the destruction of human communities: new theoretical perspectives - Greenland, Fiona; Göçek, Fatma Müge (Mass violence in modern history, 2020)
"This volume brings together leading sociologists and anthropologists to break new ground in the study of cultural violence. First sketched in Raphael Lemkin's seminal writings on genocide, and later systematically defined by peace studies scholar Johan Galtung, the concept of cultural violence seeks to explain why and how language, symbols, rituals, practices, and objects are so frequently in the crosshairs of socio-political change. Recent conflicts in the Middle East, Africa, and Central Asia, along with renewed public interest in the repertoire of violence applied to the control and erasure of indigenous populations, highlights the gaps in our understanding of why cultural violence occurs, what it consists of, and how it relates to other forms of collective violence"--